Influence of low-spin Co3+ for high-spin Fe3+ substitution on the structural, magnetic, optical and catalytic properties of hematite (α-Fe2O3) nanorods. (May 2021) - Popov, Nina; Bošković, Marko; Perović, Marija; Németh, Zoltán; Wang, Junhu; Kuang, Zhichong; Reissner, Michael; Kuzmann, Ernő; Homonnay, Zoltán; Kubuki, Shiro; Marciuš, Marijan; Ristić, Mira; et al.
Abstract: Pure hematite nanorods and very long and thin cobalt-doped hematite nanorods (nanoneedles) were prepared by a combined precipitation and annealing method. The influence of the level of cobalt doping on different properties of hematite nanorods was investigated. Incorporation of cobalt in the form of low-spin Co 3+ ions into the structure of hematite by substitution for high-spin Fe 3+ ions was proved by determination of a significant unit cell contraction by powder X-ray diffraction (PXRD) and characteristic positions of the absorption edge in X-ray absorption near edge structure (XANES) spectra and peaks in X-ray emission (XES) spectra. Cobalt doping caused a gradual elongation and thinning of hematite nanorods – very long and thin 1D nanoparticles (nanoneedles) were formed in the presence of 10 and 12 mol% Co. Magnetic measurements showed a strong increase in low-temperature remanent magnetization and coercivity upon cobalt doping, as well as a disappearance of the Morin transition, which was also confirmed by Mössbauer spectroscopy. Cobalt doping significantly affected optical properties of hematite nanorods – absorption in the visible and NIR ranges increased, which was accompanied by narrowing of the optical band gap. Compared with pure hematite nanorods cobalt-doped hematite nanoneedles showed a significantly better electrocatalytic activity for the oxygen evolution reaction (OER). Highlights: 1D cobalt-doped hematite (α-Fe2 O3 ) nanoparticles were prepared and characterized. Low-spin Co 3+ -for-Fe 3+ substitution in hematite up to 12 mol% was determined. Morin transition in hematite nanorods disappeared by cobalt doping. Remanence and low-temperature coercivity strongly increased with cobalt doping. Cobalt doping reduced photocatalytic and enhanced electrocatalytic activity of hematite.